Role of Trehalose in Salinity and Temperature Tolerance in the Model Halophilic Bacterium Chromohalobacter salexigens - Reina-Bueno, Mercedes (Public Library of Science, 2012)

(untitled)
The disaccharide trehalose is considered as a universal stress molecule, protecting cells and biomolecules from injuries imposed by high osmolarity, heat, oxidation, desiccation and freezing. Chromohalobacter salexigens is a halophilic and extremely halotolerant γ-proteobacterium of the family Halomonadaceae. In this work, we have investigated the role of trehalose as a protectant against salinity, temperature and desiccation in C. salexigens. A mutant deficient in the trehalose-6-phosphate synthase gene (otsA::Ω) was not affected in its salt or heat tolerance, but double mutants ectoine- and trehalose-deficient, or hydroxyectoine-reduced and trehalose-deficient, displayed an osmo- and thermosensitive phenotype, respectively. This suggests a role of trehalose as a secondary solute involved in osmo- (at least at low salinity) and thermoprotection of C. salexigens. Interestingly, trehalose synthesis was osmoregulated at the transcriptional level, and thermoregulated at the post-transcriptional level, suggesting that C. salexigens cells need to be pre-conditioned by osmotic stress, in order to be able to quickly synthesize trehalose in response to heat stress. C. salexigens was more sensitive to desiccation than E. coli and desiccation tolerance was slightly improved when cells were grown at high temperature. Under these conditions, single mutants affected in the synthesis of trehalose or hydroxyectoine were more sensitive to desiccation than the wild-type strain. However, given the low survival rates of the wild type, the involvement of trehalose and hydroxyectoine in C. salexigens response to desiccation could not be firmly established.